2021
DOI: 10.3390/biology10090852
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acidosis in the Pathogenesis of Severe Forms of COVID-19

Abstract: COVID-19 has specific characteristics that distinguish this disease from many other infections. We suggest that the pathogenesis of severe forms of COVID-19 can be associated with acidosis. This review article discusses several mechanisms potentially linking the damaging effects of COVID-19 with acidosis and shows the existence of a vicious cycle between the development of hypoxia and acidosis in COVID-19 patients. At the early stages of the disease, inflammation, difficulty in gas exchange in the lungs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 82 publications
1
36
0
Order By: Relevance
“…These obviously include breathlessness due to low O 2 directly, and thrombotic events such as acute myocardial infarction [180,181], stroke [181][182][183], etc due to the microclots. The lack of O 2 transport to tissues explains straightforwardly how a nominally respiratory disease also leads to the dysfunction of organs such as the kidney [184,185], PoTS ( postural tachycardia syndrome [186]), myalgia in skeletal muscle [187,188], neurological disorders [189], and lactic acidosis [190,191] (the mass of lactate is too low to have been detected in our own COVID untargeted metabolomics experiments [192]), and potentially the benefits of hyperbaric O 2 therapy [193]. It is also worth stressing that amyloid structures themselves tend to be cytotoxic, often via membrane disruption [194][195][196][197][198].…”
Section: Ability Of Amyloid Microclots To Explain the Symptoms Of Lon...mentioning
confidence: 99%
“…These obviously include breathlessness due to low O 2 directly, and thrombotic events such as acute myocardial infarction [180,181], stroke [181][182][183], etc due to the microclots. The lack of O 2 transport to tissues explains straightforwardly how a nominally respiratory disease also leads to the dysfunction of organs such as the kidney [184,185], PoTS ( postural tachycardia syndrome [186]), myalgia in skeletal muscle [187,188], neurological disorders [189], and lactic acidosis [190,191] (the mass of lactate is too low to have been detected in our own COVID untargeted metabolomics experiments [192]), and potentially the benefits of hyperbaric O 2 therapy [193]. It is also worth stressing that amyloid structures themselves tend to be cytotoxic, often via membrane disruption [194][195][196][197][198].…”
Section: Ability Of Amyloid Microclots To Explain the Symptoms Of Lon...mentioning
confidence: 99%
“…to manipulate and evade the host immune system [ 71 , 73 , 80 ]. COVID-19 patients with poor clinical outcomes or severe cases were found to have elevated levels of blood lactate [ 81 ] and increased levels of acid in blood and body tissues, i.e., acidosis [ 82 ]. When Candida spp.…”
Section: Factors That Predispose Candidiasis In Covid-19 Patientsmentioning
confidence: 99%
“…It is known that diabetes triggers an exaggerated inflammatory syndrome, which suggests that in combination with an autoimmune disease, such as RA, the outcome could be fatal. The decrease in oxygen saturation leads to increased acidosis, which in turn might change the conformation of the virus’ S-protein and lower the antibody affinity and protection [ 68 , 69 ]. Prolonged studies across Europe have reported that populations aged 18 and younger were more likely to receive a diabetes diagnosis after more than 30 days post-infection, whereas in the general population it is a common complication to receive a type 1 diabetes diagnosis or an increase in diabetic ketoacidosis [ 32 ].…”
Section: Orthopedic Conditions and Covid-19mentioning
confidence: 99%